Accountability of armed opposition groups in international law - Zegveld, Liesbeth (Cambridge studies in international and comparative law., 2002)
Most conflicts are internal, yet under international law, accountability for acts committed by armed groups is unclear. These groups should be legally identified, argues Liesbeth Zegveld, in this award-winning scholarship. Of interest to academics, postgraduate students and professionals involved with armed conflict and international relations.